Design and Development of a High-and-Low-Altitude Air Observation System for Rainmaking Process in Thailand - P. Chodkaveekityada; P. Wardkein (My University, 2019)
Thailand has been known as a top agricultural exporter in the world.But in every year, we miss a lot of opportunities to export some agricultural products due to drought condition.In the years 2017 and 2018, the areas in risk of a drought crisis were 47 areas throughout the whole country amounting to around 1.5 million acres.There was not enough water to grow plants in these areas.As a matter of fact, Thailand is located near the equator which has more cumulative rainfall volume than any other areas in the world.Still, drought crisis happens every year.One of the reasons behind this may be lack of valid predictive information.Weather information is very important for an agricultural country.Thailand has not invested sufficiently in building an effective weather sensor network.A compromise has been made by employing high technology to produce rain in specific areas instead to alleviate drought crisis.This work was a design and development of a high-and-low-altitude air observation system suitable for rainmaking process in Thailand that aimed to reduce the import of advanced and expensive technology. Index Terms-Rainmaking, high-and-low altitude
Keywords: Water Quality Monitoring Technologies